Improving Critical Care Teamwork: Simulation-Based Interprofessional Training for Enhanced Communication and Safety - Sung TC; Hsu HC (Journal of Multidisciplinary Healthcare)
Tzu-Ching Sung,1 Hsiang-Chin Hsu2,3 1School of Medicine for International Students, College of Medicine, I-Shou University, Kaohsiung, Taiwan; 2School of Medicine, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 3Department of Emergency Medicine, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, TaiwanCorrespondence: Hsiang-Chin Hsu, School of Medicine, College of Medicine, National Cheng Kung University, 138 Sheng-Li Road, Tainan, 70428, Taiwan, Tel +886 6 2353535 ext. 2237, Fax +886 6 2749095, Email i3593120@gmail.comBackground: This study evaluates a simulation-based interprofessional education (IPE) program implemented at the National Cheng Kung University Hospital between 2018 and 2023. The program aimed to improve teamwork, communication, and collaboration among healthcare professionals in high-acuity environments such as emergency departments and intensive care units (ICUs).Methods: A prospective, mixed-methods approach was used to assess the program’s effectiveness. The study enrolled 237 participants, including postgraduate medical trainees, nurses, respiratory therapists, and administrative staff. Two high-fidelity clinical scenarios—multiple trauma and respiratory distress with shock—were designed to simulate real-world emergencies. Participants’ teamwork performance was evaluated using the Team Emergency Assessment Measure (TEAM), while qualitative feedback was collected via structured questionnaires and thematically analyzed.Results: Quantitative analysis revealed significant improvement in leadership communication (p = 0.0328) and positive trends in teamwork dimensions such as completion and effective communication. However, global team performance showed only modest numerical gains. (p=0.5201) Qualitative feedback highlighted recurring themes such as unclear task delegation, delayed recognition of patient condition changes, and inconsistent use of communication techniques like call-outs and check-backs.Conclusion: The simulation-based IPE program significantly enhanced interprofessional collaboration and clinical competencies among participants. However, specific areas, particularly communication, leadership, and situational awareness, require further attention in future training sessions. These findings underscore the importance of continuous refinement of simulation programs to prepare healthcare teams for high-stakes clinical scenarios effectively.Keywords: interprofessional education, simulation-based learning, teamwork, healthcare collaboration, patient safety